Manajemen Peran Guru BK dalam Meningkatkan Motivasi Belajar Siswa Kelas XI MIPA SMA Negeri 1 Cigugur - Rosiva Febrian; Azlika Avilla Mutia; Asep Saepudin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This study aims to determine the role of guidance and counseling teachers in improving learning motivation. The research method used is a qualitative descriptive research method that produces descriptive data on phenomenological studies. Data collection techniques in this study used observation, interview and documentation techniques. Learning motivation is a crucial factor in student success in education. This study identified that at SMAN 1 Cigugur, some students have low learning motivation, which is influenced by internal and external factors such as family environment and interaction with teachers. The role of Guidance and Counseling teachers is very important in helping students overcome problems through various services such as individual guidance and counseling, group guidance and counseling, and collaboration with subject teachers. BK teachers at this school provide information services as the main strategy to improve student learning motivation. The results of the study indicate that guidance and counseling teachers play a very important role in improving student learning motivation